Penerapan Model Advance Organizer untuk Peningkatan Minat dan Prestasi Belajar Matematika - Palobo, Markus; Nurhayati, Nurhayati; Rhamadani, Via (Musamus Journal of Mathematics Education, 2020)
This research is a classroom action research that aims to increase interest and achievement of learning mathematics using Advance Organizer model. This research was conducted in two cycles with 4 meetings in each cycle. Subjects in the study consisted of 28 students, 17 male students and 11 female students of grade IX SMP Negeri 2 Merauke. Data collection techniques used are test techniques for achievement tests and non-test techniques for interest questionnaires and observation sheets. The result of the research is the interest of learning mathematics of students in cycle I was 64,29% which is in good category and very good and in cycle II student learning interest increased to 78,58% which is in good category and very good. Student learning achievement in pre cycle with the value above 61 was 35,71% complete. In the first cycle student achievement increased by 53.57% of students value above 61 and on the second cycle student achievement increased to78.57% of students who reached Minimum Mastery Criteria (KKM). Based on the result, it can be concluded that Advance Organizer model can increase interest and achievement of mathematics learning of grade IX students of SMP Negeri 2 Merauke.